The application of Sugeno fuzzy to control active power load and remaining battery usage time modelling - Wahyu Setyo Pambudi; Riza Agung Firmansyah; Rizal Rahmanto Issany; Ryan Yudha Adhitya; Mat Syai'in (Indonesian Journal of Electrical Engineering and Computer Science, 2022)
This study aimed to propose a control scheme to optimize the active power load using the pulse-width adjustment technique and the MOSFET driver. The power used and stored in the battery is an input for the fuzzy system whose information is obtained through the current (ACS 712) and voltage sensor readings. The use of fuzzy to control the power of two 5-watt lamps is more efficient than the manual technique using an ordinary switch. This is because fuzzy only consumes 3.25 Watt/hour while the manual technique requires 5.7 Watt/hour. Based on the linear regression-based estimation, the fuzzy technique lasts ±17 hours from the initial power of 55.82 Wh, or 5.5 hours longer than the manual technique that lasts only ±11.5 hours from the initial power of 65.62 Wh. Therefore, this study adjusted the load power to extend battery life and increase solar energy use efficiency and innovations in load control based on available resources.